Soziale Neurowissenschaften und deren Bedeutung für die Psychiatrie - Holz, Nathalie E.; Meyer-Lindenberg, Andreas (Der Nervenarzt, 2019)
BackgroundThe social brain is dysfunctional in numerous stress-related psychiatric disorders.ObjectiveThe definition of social brain networks and their susceptibility for social environmental stress. It is also reviewed how social brain networks are disrupted in schizophrenia, autism and conduct disorder.Material and methodsLiterature search in PubMed.ResultsThe social brain consists of several subnetworks that act in concert to foster empathy. Interestingly, except for the mirror neuron system, the neural networks of the social brain have been reported to be vulnerable to social environmental stress and have also been highlighted as being compromised in psychiatric disorders. As an example, schizophrenia is related to dysfunction in social perception, mentalizing, and affiliation, whereas the most pronounced deficits in autism are seen during social perception and mentalizing. Patients with conduct disorder are more prone to dysfunction in perception, affiliation and aversion.ConclusionSocial stress affects subnetworks also compromised in psychiatric disorders. Therefore, it is plausible that the social brain might mediate the association between social stress and psychiatric disorders. To advance ecological validity in social neuroscience, recent research has highlighted the role of hyperscanning and virtual reality as means by which a more naturalistic assessment of social interactions might be feasible.
Englische Zusammenfassung: The importance of social neurosciences for psychiatry
Gesehen am 16.12.2019